Stress in soldiers in stabilisation operations and support peace beyond country borders - Barć, Marek; Kapelewska – Barć, Aleksandra (Polityka i Społeczeństwo, 2024)
This article is devoted to the stress experienced by soldiers serving abroad. The first part of the article discusses stress as a social phenomenon followed by a presentation of the history of combat stress over the centuries and ways of understanding it. The terminology of stress and combat stress is presented in different approaches. In the second part, the terminology of war stressors, i.e. stressors that can occur on missions abroad, is presented. The final section divides stressors into physical, cognitive, social, emotional and spiritual stressors and briefly characterises them1.